FATIGUE TESTING OF IMPLANT SUPPORTED ZIRCONIA REINFORCED LITHIUM SILICATE CROWN - Noochudom, Nuttarut; Keeratihattayakorn , Sarun; Padipatvuthikul Didron, Pavinee; Puengpaiboon, Usanee (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The purpose of this study was to evaluate fatigue limit of implant-supported zirconia reinforced lithium silicate (ZLS) crown. Eleven implant-supported ZLS crowns (Implant diameter 5 mm x 10 mm in length) were fabricated for fatigue limit test using a standard fatigue tester. Following ISO 14801: 2016, samples were tested at 37๐C in 0.9% saline at 15 Hz until failure or reach 5x106 cycles. Three samples were subjected to static load for evaluation of single load to failure. Nominal peak levels at 10%, 20%, 30%, 40% of previously obtained static failure load were used for fatigue limit test. Two samples were tested at each load until catastrophic failure or the maximum of 5x106 cycles were reached. The mean failure load was 1,316.68 ± 50.59 N and the fatigue limit was 395 N. The fracture of failed samples was found only at the crowns, no failure was observed in implant components. In conclusion the fatigue limit value of implant-supported ZLS crowns obtained from this study show that ZLS can be used efficiently as restoration on dental implant from incisor to canine region for up to 5 years.